Orginal articleBrachial plexus injuries after radiotherapy – analysis of 6 cases - Gosk, Jerzy; Rutowski, Roman; Urban, Maciej; Wiącek, Roman; Rabczyński, Jerzy (Folia Neuropathologica, 2007)
Radiation-induced brachial plexus neuropathy is caused by compression of the nerve fibres by dense and inelastic fibrous connective tissue. In this study our own experience in treatment of lesions of the brachial plexus after radiotherapy is presented. The clinical material consisted of 6 patients aged from 40 to 64 years with injuries of the brachial plexus after radiotherapy. The analysis of the material comprised: basic disease, duration of radiotherapy, radiated fields, total dose of radiation, onset and character of symptoms, location and severity of injury. 5 women were qualified for surgical treatment. After neurolysis of the brachial plexus a significant improvement was obtained in 2 cases. In one patient remission of pain and sensory recovery was temporary. No improvement was observed in the remaining 2 patients. Lesions of the brachial plexus after radiotherapy are rare but difficult to prevent. The treatment depends on the grade of severity of injury. Surgical neurolysis is advised for grades 3 and 4 on the LENT-SOMA scale.